2022
DOI: 10.1037/ort0000582
|View full text |Cite
|
Sign up to set email alerts
|

Examining risk and protective predictors of substance use among low-income Native Hawaiian and Pacific Islander adolescents.

Abstract: Substance use (SU) among adolescents is a critical public health concern that increases the risk for negative outcomes. Although Asian American (AA) adolescents tend to report low rates of SU, Native Hawaiian and Pacific Islander (NH/PI) adolescents often report significantly higher rates of use. Yet, NH/PI youth are seldom studied as a separate group. Consequently, little is known about the factors involved in SU among NH/PI adolescents and how to prevent it. This prospective study investigated the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Studies have suggested differences in protective factors for substance use between NHPI and Asian American adolescents—with parental support acting as a positive buffer against engaging in substance use among Asian American adolescents but with conflicting evidence for such protection among NHPI adolescents. 5,15,16 Wills et al noted that their measurement model narrowly defined a nuclear NHPI parental system and could be improved by including extended family members given the potential influence of other family members on the social environment of NHPI adolescents and their decisions on substance use. 16 Substance use among Asian American students may be explained by acculturative stress, correlated with differential rates of alcohol use; acculturation has been associated with increased alcohol consumption among Asian American students.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have suggested differences in protective factors for substance use between NHPI and Asian American adolescents—with parental support acting as a positive buffer against engaging in substance use among Asian American adolescents but with conflicting evidence for such protection among NHPI adolescents. 5,15,16 Wills et al noted that their measurement model narrowly defined a nuclear NHPI parental system and could be improved by including extended family members given the potential influence of other family members on the social environment of NHPI adolescents and their decisions on substance use. 16 Substance use among Asian American students may be explained by acculturative stress, correlated with differential rates of alcohol use; acculturation has been associated with increased alcohol consumption among Asian American students.…”
Section: Discussionmentioning
confidence: 99%
“…21-23 One study of NHPI adolescents identified several significant protective factors for substance use among NHPI adolescents in the school context, such as school-based programs, teachers as role models, and peer relationships. 5…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations